Zeolites in acid vitreous rocks, southern Mendoza, Argentina. (March 2020) - Locati, Francisco; Cravero, Fernanda; Marfil, Silvina; Lescano, Leticia; Madsen, Lenís; Maiza, Pedro
Abstract: A mordenite-rich deposit located in the south of the province of Mendoza (Argentina) was studied. The host rock in this area has not been previously described and corresponds to rhyolitic lavas of high-K calc-alkaline series. Petrographic, mineralogical and geochemical analyses of fresh and altered rocks are shown, and a proposal for the alteration process and the stratigraphic position of the protolith is presented. The main mordenite-rich sectors developed in zones of autobreccias of high permeability, with minor clinoptilolite, smectites, secondary K-feldspars, opal-CT, and colloform silica. The proportion of relict glass vs. alteration minerals is variable and mainly depends on the texture (permeability) of the host rock. The studied rhyolites overlie the Upper Cretaceous sediments of the Neuquén Group and are covered by Tertiary basalts of the Molle Eruptive Cycle and Quaternary sediments. Geochemically, they present similarities with rhyolitic rocks of Cordón del Burrero Volcanic Complex of Lower to Middle Miocene age. Highlights: A rhyolitic complex from the province of Mendoza (Argentina) is studied. Zones of high permeability in autobreccias host a mordenite-rich deposit. Associated phases comprise clinoptilolite, smectites, K-feldspars and colloform silica. Host rocks correspond to rhyolitic magmas of high-K calc-alkaline series. A correlation with rhyolites of Cordón del Burrero Volcanic Complex is proposed.